Reversible Vision Loss In A Patient With Infective Endocarditis - Saba Zaidi; Abubakr; Uzma Ghori (ziauddin University, 2024)
Visual complications in patients with infective endocarditis include central retinal artery or vein occlusion, corneal ulcers, endophthalmitis, sub-retinal abscess, papillitis, optic neuritis and cortical blindness due to septic micro-embolization. Although there is no epidemiological data available on the visual complications of infective endocarditis, however, many case reports reveal that these are common and could be the first presentation of infective endocarditis. We presented a case of a young gentleman, an intravenous drug abuser who presented with fever and bilateral, painless, vision loss. Fundoscopic examination revealed Roth spots. Echocardiography showed vegetation on anterior mitral leaflet. Blood cultures showed growth of Staphylococcus Aureus. His MRI brain showed small areas of diffusion restriction in bilateral parieto-occipital regions.The patient receivedbroad spectrum antibiotics for native valve endocarditis. His vision improved after 18 hours of hospital stay. We emphasize the importance of recognizingthe visual complications in patients with infective endocarditis. Early diagnosis leads to early treatment and reversibility of this focal deficit. Key Words: Vision, Endocarditis, Early diagnosis